1996
DOI: 10.1088/0022-3727/29/10/006
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and preferential sputtering of Al on (100)

Abstract: Using 1 - 2 keV and 1.5 - 3 keV beams, the measurement of the first layer composition of (100) at room temperature reveals a slight enrichment of Al on the surface. The enrichment of Al at room temperature also was confirmed by analysis using a 2 keV beam. It was found that Al atoms on the surface were preferentially sputtered for 1 - 2 keV and 1.5 - 3 keV beams. The surface concentration of Al increased with temperature in the range 300 - 620 K due to the combined effect of preferential sputtering, ion b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…[14] In that study, Al was found to be preferentially sputtered from the alloy surface. In addition, the ratio of the Al and Cu surface compositions increased with temperature over a range from 20 to 350 • C for the surface irradiated with 3 keV Ne + .…”
Section: Resultsmentioning
confidence: 89%
“…[14] In that study, Al was found to be preferentially sputtered from the alloy surface. In addition, the ratio of the Al and Cu surface compositions increased with temperature over a range from 20 to 350 • C for the surface irradiated with 3 keV Ne + .…”
Section: Resultsmentioning
confidence: 89%
“…Previous works reported that the composition of the clean a-Cu-Al (1 0 0) surface is similar to the bulk composition [5,6], or has a slight segregation of Al to its surface [7][8][9]. Electron and ion spectroscopy measurements of clean aCu-Al(1 0 0) alloys show that no Al islands form on its surfaces [10,11], but after oxidation Al oxide islands were formed upon heating the samples to 300°C [11].…”
Section: Introductionmentioning
confidence: 95%
“…From previous oxidation studies of the a-Cu-Al(1 0 0) surface for various Al concentrations [7][8][9][10][11][12] the interaction of oxygen with these surfaces may be divided into two main stages: a fast one, during which oxygen adsorption takes place mostly on top of the alloy surface, followed by a slower one, which involves oxidation-induced aluminum enrichment. For the 12% Al alloy it was determined by O(1s)-XPS measurements [7,11] that during the fast stage of exposure, oxygen reacts first with Al sites forming Al-O bonds, followed by reaction with Cu sites forming Cu-O bonds upon larger exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A mosaic target was employed with bulk Fe 70 Sn 30 alloy and SiO 2 in which small pieces of Fe 70 Sn 30 adhered compactly to the plate of SiO 2 . Different values for the Fe concentration, x, were obtained by making use of the phenomena of preferential sputtering [9], due to the different sputtering rates for Fe and Sn. As the sputtering rates between Fe and Sn is different, after some period of sputtering time, the concentration of the Fe-Sn alloy might have changed from the original ratio.…”
Section: Methodsmentioning
confidence: 99%